(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objectives: This study was conducted to discover the treatment outcome and side effects of chronic hepatitis C virus patients treated with Direct-Acting Antivirals (DAAs). Methods: Based on the Liver Center database, we studied the treatment effect of Sofosbuvir 400 mg/Ledipasvir 90 mg in 1109 patients with chronic hepatitis C virus infection during the time period from December 2015 to December, 2018. Results: In patients treated with Sofosbuvir/Ledipasvir, the sustained viral load (SVR12) was 97.9% (1086/1109) 12 weeks after the treatment. The SVR12 was 99.2% (845/851) in HCV-infected non-cirrhotic patients, 93.4% (241/258) in patients with cirrhosis, and 80% (8/10) among patients treated for liver cancer. The SVR12 (19/25) was lowered to 76% at 12 weeks of treatment with Sofosbuvir 400 mg/ Daclatasvir 60 mg in DAA-failure patients 23/1109 (2.07%). Conclusions: SVR12 rates in non-cirrhotic and cirrhotic patients were 99.2% and 93.4%, respectively, while it was 80% in liver cancer patients after DAA treatment. As for patients with viral relapse, 76% of them were successfully retreated with second-line DAA treatment. During the DAA treatment, only 17.6% of all patients had some adverse effects related to DAA treatment, thus, DAA treatment is suitable for Mongolian patients and has less adverse effects.